Analisis Kapasitas Landasan Pacu Sultan Hasanuddin International Airport - Rency Bunga Palayukan; Rais Rachman; Ari Kusuma (Paulus Civil Engineering Journal, 2020)
Sultan Hasanuddin Makassar International Airport, better known as SHIAM, has the status of a major transit airport, especially for flights to the Eastern Indonesia region. This causes the demand for demand to increase, especially when entering peak hours or during holidays, if the number of aircraft that will act at an airport exceeds capacity it will cause an overload on the Air Traffic Management (ATM) system which makes the quality of service better. given Down, for example there is a delay in the implementation of operations. The research objective is to determine the runway requirements for Boeing 737-900.ER aircraft, runways for Boeing 737-800 aircraft, and runways for Airbus A320 aircraft The results of the research on the design of the Boeing 737-900.ER aircraft meet the need for a long runway, the plan for the Boeing 737-800 aircraft meets a long runway, and the existing runway meets the use of Airbus A320 aircraft.